Tainia epiphytica sp. nov. (Orchidaceae), a new species from North East India - Sarkar, Shuvadip; Agrawala, Dinesh Kumar; Chakraborty, Sayak; Maity, Debabrata; Odyuo, Nripemo (Phytotaxa, 2023)
A new species of Tainia, Tainia epiphytica sp.nov. (Orchidaceae) is described and illustrated based on specimens from Mizoram and Nagaland, North-East India. Morphologically, the new species is similar to Tainia bicornis, Tainia dunnii and Tainia latifolia but differs in many attributes which are discussed here. An updated key for all the species of Tainia found in India is provided for easy identification.